THE FINANCING RESTRUCTURING LEGAL ANALYSIS FOR DEBTORS AFFECTED BY COVID-19 IN SHARIA MULTIFINANCE INSTITUTIONS - Andi Aina Ilmih; Kami Hartono; Ida Musofiana (UNISSULA, 2021)
This study focuses on problematic financing by debtors affected by Covid-19 at Islamic multi-finance institutions in Semarang City, with the aim of finding the reality of the form of problematic financing experienced by debtors during the Covid-19 Pandemic. This study uses an empirical juridical approach, data analysis using descriptive-analysis methods. Based on the research that has been done, the regulation of the Financing Restructuring Law is guided by POJK Number 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy on the Impact of Coronavirus Disease 2019 which regulates asset determination, financing restructuring and provision of new funds. The impact arising from the existence of a financing restructuring policy for debtors affected by Covid-19 can be viewed from the following aspects: (1)Juridical Aspect, meaning that there are no sanctions for the financing institution as a creditor if it does not follow or apply, only based on the willingness of the creditor; (2) Economic Aspect, can help debtors to recover and stabilize the economy so that they can fulfill promises (achievements) to creditors; and for creditors the impact on financial activities or transactions that occurred during the Covid-19 pandemic can still be stable; (3)Psychological Aspects, meaning that one side fosters a strong mentality and confidence for creditors/financing customers to fulfill their obligations, and on the other hand, the existence of the presence of financial institutions is maintained in the future.